Prispevek k poznavanju razširjenosti močvirske sklednice (Emys orbicularis (Linnaeus, 1758)) ob reki Dravi v Sloveniji - Govedič, Marijan (Natura Sloveniae, 2003)
New discoveries together with published data on European pond turtle along the Drava river in Slovenia are presented. Subspecies Emys orbicularis orbicularis was confirmed for the first time in Slovenia
Keywords: biotopi; močvirska sklednica; plazilci; Podravje; reptile; Slovenia; Slovenija; zoologija; zoology; želve